Assessment and Use Features of the Forensic Experts’ Opinions in the Investigation and Trial of Iatrogenic Crimes - M. V. Tuzlukova (Теория и практика судебной экспертизы)
The article analyzes theoretical and practical aspects of assessing and using forensic experts’ opinions in investigation and trial on criminal cases of iatrogenic crimes. Summarized data on the content and stages of the experts’ opinions assessment is given, the features of the conclusions of forensic medical examinations assessment are noted. The absence of complexes of specialized forensic medical research methods of certain varieties of iatrogenic crimes concerning various medical practice areas is considered a factor that impedes the assessment of conclusions by the investigating bodies and court. The author states that evaluating expert opinions by investigators, prosecutors, and courts should not be limited to studying and analyzing only the text of the opinion. A large role is played by specialists’ involvement, interrogations of experts, and other investigative actions, together with the court examining other evidence.